Comparing The Effectiveness of Mindfulness-Based Cognitive Behavioral Therapy and Electronic Muscle Stimulation on Balance, and Psychological Wellbeing in Elderly - Ahmadpour, Maedeh; Khorand, Mohammad Taghi (AI and Tech in Behavioral and Social Sciences, 2024)
Objective: The objective of this study was to compare the effectiveness of Mindfulness-Based Cognitive Behavioral Therapy (MCBT) and Electronic Muscle Stimulation (EMS) on balance and psychological well-being in elderly women aged between 60 and 75 years. Methods and Materials: This randomized controlled trial included 135 participants, divided equally among three groups: MCBT, EMS, and a control group. Each group comprised 45 participants. The interventions lasted for three months with a subsequent three-month follow-up. Balance was assessed using the Berg Balance Scale, and psychological well-being was measured using the Psychological General Well-Being Index. Data were analyzed using a mixed-model analysis of variance (ANOVA) with repeated measurements and Bonferroni post-hoc tests, employing SPSS-27 for statistical analysis. Findings: The interventions significantly improved both balance and psychological well-being from baseline to post-intervention. EMS showed a more significant improvement in balance, with scores increasing from a pre-test mean of 20.45 (SD = 3.60) to a post-test mean of 23.78 (SD = 4.12) (p < .001). MCBT was more effective in enhancing psychological well-being, with scores improving from a pre-test mean of 68.20 (SD = 5.50) to a post-test mean of 75.45 (SD = 6.34) (p < .001). Both interventions maintained their effects at the three-month follow-up. Conclusion: Both EMS and MCBT are effective interventions for improving balance and psychological well-being in elderly women, respectively. EMS may be more suited for physical balance enhancements, while MCBT may be more effective for mental health improvements. The results suggest that integrating these interventions could potentially offer comprehensive benefits in elderly care.